Rancang Bangun Aplikasi Perekaman Data Sertifikat (Studi Kasus PT. SUCOFINDO) - M. Arika Dharma Satria; M.J. Dewiyani Sunarto; Ignatius Adrian Mastan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Abstract: PT. Superintending Company of Indonesia (Persero), or better known by the acronym PT.Sucofindo, is an Indonesian state-owned enterprises engaged in the field of inspection, supervision, testing, and assessment of export and import goods. SUCOFINDO produced a products in the form of a certificate. The problems that exist in the print process, certificate is archieving number of certificates paper are still done manually and requires a long time to recapitalize a number of certificates paper. To solve the above problems, by applying design certificate data recording application, which to make the printing officers seeks in the archives certificate number certificate paper, tracing certificates paper use and report the use of paper certificates per period. Keywords: Sucofindo, certificate, certificate data recording